USING SELF-TALK TECHNIQUE IN DEVELOPING GRADE 1 STUDENTS’ SPEAKING ABILITY IN ELEMENTARY SCHOOL - Annisa Erma; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2016)
Speaking in a foreign language is one of difficult activities for students. It is caused by some factors, which are the lack of role models, vocabulary mastery, and inability of brainstorming ideas. an appropriate technique is needed to solve these problems. One of the techniques is “self-talk” technique. This technique helps both teacher and students to built the interaction. In this technique, teacher explains what they are doing. The teacher will provide list of vocabularies to describe what they are doing. This technique is expected to help students in speaking, because speaking starts after listening. In addition, the teacher gives direct examples of the vocabulary to help students develop the ideas they are going to say. The difficulties that are faced by the students is expected to be solved through this technique.